2021
DOI: 10.1021/acs.langmuir.1c01124
|View full text |Cite
|
Sign up to set email alerts
|

Novel Environmentally Friendly Waterborne Epoxy Coating with Long-Term Antiscaling and Anticorrosion Properties

Abstract: Metal pipes in industrial production are exposed to various corrosive ions. The combined action of these ions with oxygen in water causes corrosion and contamination of the metal pipes and equipment. In addition, metallic ions in water react with anions to form scale on the surface of the metal, which significantly reduces the service life of the metal and equipment, resulting in safety hazards. Waterborne coatings have attracted tremendous attention due to the less negative impact on the environment, but thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The rate of loading of sodium phytate was found to be 25.79 wt% and the fastest release was observed at a pH of 9 [101]. The slow-release of nanofiller Lecithin-SiO2-Etidroic acid introduced into WEP coating was analyzed by Wang et al The synthesized nanofiller showed one order greater magnitude of impedance with the maximum inhibition efficiency of 80.7% [102]. Different corrosion inhibitors incorporated into various nanocontainers/microcontainers are illustrated in Table 3.…”
Section: Smart Coatingmentioning
confidence: 99%
“…The rate of loading of sodium phytate was found to be 25.79 wt% and the fastest release was observed at a pH of 9 [101]. The slow-release of nanofiller Lecithin-SiO2-Etidroic acid introduced into WEP coating was analyzed by Wang et al The synthesized nanofiller showed one order greater magnitude of impedance with the maximum inhibition efficiency of 80.7% [102]. Different corrosion inhibitors incorporated into various nanocontainers/microcontainers are illustrated in Table 3.…”
Section: Smart Coatingmentioning
confidence: 99%
“…Due to the multiple advantages such as good formability, and chemically inert and oil-absorbing properties, 41 polydimethylsiloxane (PDMS) was firstly selected to prepare a microspine To ensure that all values are comparable, scale-resistant performance is evaluated by comparing scale mass gain or coverage percent on the tested surface with that on the control surface after testing in a scaling solution. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][33][34][35][36][37][38] coating with a hexagonal array and rough microgrooves (Fig. S2b, ESI †).…”
Section: Characterization Of the Block Coatingmentioning
confidence: 99%
“…7,8 However, conventional scale-resistant strategies, such as mechanical descaling 9 and chemical detergents 10 often bring about plant shutdown and environmental pollution. Alternatively, superwettable surfaces 11 as functional coatings, such as superhydrophobic surfaces, [12][13][14][15][16][17][18][19][20][21][22] superhydrophilic surfaces 23 and liquid-infused surfaces, [24][25][26][27] have shown improved anti-scaling performance by mainly tuning the surface energy and surface morphology. In actual oil recovery and transportation, the produced water is often composed of complex multi-phases including oil products, water, salt ions and scales.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations